Perioperative FOLFOX in management of peritoneal metastases of colorectal cancer. Case report of 2 patients. (2020) - Sugarbaker, Paul H.; Stuart, O. Anthony
Highlights: Peritoneal metastases from colorectal cancer are lethal. Cytoreductive surgery plus perioperative chemotherapy is a treatment option. A perioperative FOLFOX regimen with intraperitoneal oxaliplatin was described. The pharmacokinetic studies suggested efficacy. Abstract: Introduction: Colorectal cancer can disseminate malignant cells to the peritoneal surfaces which over time progress to peritoneal metastases. Management of this type of metastatic disease has been approached using a combined treatment that consists of cytoreductive surgery and perioperative chemotherapy. To optimize these treatments a more effective chemotherapy that is used as planned part of the surgical procedure is required. Presentation of cases: Pharmacologic studies to initiate a new perioperative chemotherapy treatment were modeled after the successful systemic treatments of metastatic colorectal cancer referred to as FOLFOX. A management plan that included all of the essential features of successful systemic chemotherapy was formulated. Pharmacokinetic studies of 5-fluorouracil given both intravenously and intraperitoneally and oxaliplatin given intraperitoneally were investigated. Discussion: The compatibility of 5-fluorouracil and oxaliplatin was documented showing no degradation of either drug when they were mixed in-vitro over 24 h. The pharmacokinetic analysis of hyperthermic intraperitoneal chemotherapy (HIPEC) with oxaliplatin showed cytotoxic concentrations for 120 min. In order to maximize oxaliplatin's effect, both intravenous bolus and continuous infusion 5-fluorouracil was combined with early postoperative intraperitoneal chemotherapy (EPIC). In total, 200 mg/m 2 of oxaliplatin was combined with a minimum of 1600 mg of 5-fluorouracil over the 24 -h treatment plan. Conclusion: This perioperative FOLFOX treatment was completed in 2 patients and the clinical effectiveness as a result of this in-depth case reports was presented. Formal phase II studies, as a result of these pharmacokinetic and clinical investigations, have been initiated.